Expression of scavenger receptor MARCO defines a targetable tumor‐associated macrophage subset in non‐small cell lung cancer. Issue 7 (13th May 2018) - La Fleur, Linnéa; Boura, Vanessa F.; Alexeyenko, Andrey; Berglund, Anders; Pontén, Victor; Mattsson, Johanna S.M.; Djureinovic, Dijana; Persson, Johan; Brunnström, Hans; Isaksson, Johan; Brandén, Eva; Koyi, Hirsh; et al.
Abstract : Tumor‐associated macrophages (TAMs) are attractive targets for immunotherapy. Recently, studies in animal models showed that treatment with an anti‐TAM antibody directed against the scavenger receptor MARCO resulted in suppression of tumor growth and metastatic dissemination. Here we investigated the expression of MARCO in relation to other macrophage markers and immune pathways in a non‐small cell lung cancer (NSCLC) cohort ( n = 352). MARCO, CD68, CD163, MSR1 and programmed death ligand‐1 (PD‐L1) were analyzed by immunohistochemistry and immunofluorescence, and associations to other immune cells and regulatory pathways were studied in a subset of cases ( n = 199) with available RNA‐seq data. We observed a large variation in macrophage density between cases and a strong correlation between CD68 and CD163, suggesting that the majority of TAMs present in NSCLC exhibit a protumor phenotype. Correlation to clinical data only showed a weak trend toward worse survival for patients with high macrophage infiltration. Interestingly, MARCO was expressed on a distinct subpopulation of TAMs, which tended to aggregate in close proximity to tumor cell nests. On the transcriptomic level, we found a positive association between MARCO gene expression and general immune response pathways including strong links to immunosuppressive TAMs, T‐cell infiltration and immune checkpoint molecules. Indeed, a higher macrophage infiltration was seen in tumors expressing PD‐L1, and macrophages residing within tumor cell nests co‐expressed MARCO and PD‐L1. Thus, MARCO is a potential new immune target for anti‐TAM treatment in a subset of NSCLC patients, possibly in combination with available immune checkpoint inhibitors. Abstract : What's new? Because of their dual anti‐ and proinflammatory role, tumor‐associated macrophages (TAMs) are attractive targets for immunotherapy. Treatment with antibodies targeting the scavenger receptor MARCO has previously been shown to result in a more proinflammatory macrophage phenotype and reduced tumor growth. Here, the authors show that MARCO defines a distinct subset of immune‐suppressive TAMs in a large lung cancer cohort. A higher macrophage infiltration was observed in tumors expressing PD‐L1, and transcriptomic data revealed a correlation between MARCO, checkpoint molecules and T‐cell infiltration. MARCO could thus be a potential new immune target for anti‐TAM treatment in a subset of NSCLC patients.